Protecting Children Online? Cyberbullying Policies of Social Media Companies - Milosevic, Tijana (The Information Society Series, 2018)
This book investigates regulatory and social pressures that social media companies face in the aftermath of high profile cyberbullying incidents. The author's research evaluates the policies companies develop to protect themselves and users. This includes interviews with NGO and social media company reps in the US and the EU. She triangulates these findings against news, policy reports, evaluations and interviews with e-safety experts. This book raises questions about the legitimacy of expecting companies to balance the tension between free speech and child protection without publicly revealing their decision-making processes. In an environment where e-safety is part of the corporate business model, this book unveils the process through which established social media companies receive less government scrutiny than start-ups. The importance of this research for law and policy argues for an OA edition to ensure the work is widely and globally accessible to scholars and decision makers.